Comparative Analysis of Kakawin Sutasoma and The Short Story “Kepergian Sutasoma” By Gunawan Maryanto - Janah, Nadia Mawar (Jurnal Indonesia Sosial Sains, 2025)
This study compares Kakawin Sutasoma by Mpu Tantular with the short story "Kepergian Sutasoma" by Gunawan Maryanto, published in Koran Tempo on June 5, 2011. This short story tells the search for identity for Sutasoma, heir to the throne of the Hastinapura Kingdom, who chooses to exile himself. The short story was inspired by Kakawin Sutasoma, a classical Javanese literary work rich in Buddhist teachings and written during the 14th-century Majapahit era. This study aims to analyze the similarities and differences between the two, particularly in terms of story elements and narrative structure. The method used is descriptive qualitative, with data collection techniques such as document recording. The research focuses on the inspiration for Kakawin Sutasoma in the short story, the similarities between the opening section (Manggala Kakawin) and the opening of the short story, and a comparison of the narrative structures of the two. The structural analysis of the short story includes theme, setting, characters and characterization, and point of view. The results of the study show that although the short story follows the original figures and characters of Kakawin Sutasoma, the form of presentation is different because the short story is modern prose.